A Novel Neonatal Feeding Intolerance and Necrotizing Enterocolitis Risk–Scoring Tool Is Easy to Use and Valued by Nursing Staff. (June 2016) - Naberhuis, Jane; Wetzel, Christine; Tappenden, Kelly A.
Abstract : Background: Preterm infants are at increased risk of developing feeding intolerance and necrotizing enterocolitis. Comprehensive, targeted nursing assessments can evaluate the risk for and identify early signs of these conditions in an effort to prevent their destructive sequela. Purpose: While the long-term goal is to develop a validated risk-scoring tool for the prediction of feeding intolerance and necrotizing enterocolitis, the objective of the preliminary phase presented here is to assess the ease of use and nurses' attitudes toward a novel feeding intolerance and necrotizing enterocolitis risk–scoring tool. Methods: A novel risk-scoring nursing tool was implemented in a University of Illinois–affiliated 48-bed level III neonatal intensive care unit. Data were collected from the electronic medical record of all preterm infants with parental consent during the initial 6-month study period. Scoring accuracy (accuracy of selection of risk factors based on electronic medical record data), ease of use, and nurses' attitudes toward the tool were assessed at the study site and by evaluators at a national neonatal nursing conference. Results: Fourteen nurses scored 166 tools on the 63 enrolled infants. Sixteen tools (9.6%) contained errors. Mean study site tool ease of use was 8.1 (SD: 2.2) on a 10-point scale. Ninety percent of conference evaluators agreed/strongly agreed that the tool addressed important knowledge gaps. Implications for Practice: The tool is easy to use and valued by nurses. Following validation, widespread implementation is expected to be a clinically feasible means to improve infant clinical outcomes for minimal time and financial cost. Implications for Research: Tool validation and refinement based on nursing feedback will improve its broad applicability and predictive utility.